ACOPLAMENTO MEF-MDF PARA SOLUÇÃO DE PROBLEMAS VIBROACÚSTICOS 2D - Burgos, Renan Godoy (2017)
Problems related to Fluid-Structure Interaction (IFE) are present in many practical cases in Engineering. In this sense, dams reservoirs, sluices, navigation channels and columns of offshore platforms and wind turbines are some examples. The effect generated by the fluid over the structure has a key importance, because it changes its behavior and adds other forces, and so it’s indispensable an analysis of the coupled system in order to improve the development of projects. Nowadays, because of the progress in computer industry, the numerical and computational tools are fairly efficient means to perform these evaluations. Among the most used numerical methods, there are the Finite Differences Method (FDM), the Finite Element Method (FEM) and the Finite Volume Method (FVM). This paper presents a code developed with FEM-FDM coupling for the solution of the interaction of an acoustic cavity and a flexible environment (elastic). The structural domain, which is ruled by the 2D elasticity equations, is evaluated using Constant Strain Triangle (CST) finite elements, while the fluid, ruled by Helmholtz equation, is evaluated through FDM. The code results are validated based in analytical solutions available in the literature, presenting negligible errors when used a fair sized mesh and it also has a viable processing time that makes the program usable.